2021
DOI: 10.1186/s12957-021-02367-3
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of angiogenesis subtype of squamous cell carcinoma

Abstract: Background Squamous cell carcinoma (SCC) is a disease with distinct management complexities as it displays a remarkably heterogeneous molecular subtype. However, the landscape of angiogenesis for SCC is not fully investigated. Method and materials The angiogenesis-related subtypes of SCC were established by using the ConsensusClusterPlus package based on angiogenesis-related genes and TCGA data. We analyzed the alteration of genes and miRNAs as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Strategies to improve patient prognosis and quality of life deserve further study. It is reported that abnormal expression of important genes and alterations of signaling pathways are associated with cancer pathogenesis [ 23 , 24 ]. For instance, Qin F et al revealed a novel angiogenesis subtype classification in squamous cell carcinoma [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strategies to improve patient prognosis and quality of life deserve further study. It is reported that abnormal expression of important genes and alterations of signaling pathways are associated with cancer pathogenesis [ 23 , 24 ]. For instance, Qin F et al revealed a novel angiogenesis subtype classification in squamous cell carcinoma [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Qin F et al revealed a novel angiogenesis subtype classification in squamous cell carcinoma [ 23 ]. Li S et al screened six prognostic hub genes by weighted gene co-expression network analysis (WGCNA) combined with LASSO Cox-PH analysis, which provided a new strategy for targeted therapy of cervical cancer [ 24 ]. The study aimed to explore the molecular mechanism of cervical cancer and find new tumor markers and biological methods to treat tumors .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we speculate that 3 IRLs (BARX1-DT, KLHL7-DT, and LINC02154) may boost the development of an immunosuppressive TME by thoroughly downregulating the expression of key immunomodulators such as CCR3, CXCL10, and CXCL9 and subsequently decreasing the recruitment of effector CD8 T cells, thereby exerting resistance to checkpoint immunotherapy. Interestingly, ssGSEA results and correlation analysis show that signaling pathways related to tumor invasion and metastasis, such as p53 signaling pathway, EMT2, EMT3, and TGF-beta signaling pathway, were mainly involved in high-risk groups, which are recognized as immunosuppressive and play a key role in tumorigenesis [ 26 ]. However, CD8 T effector was significantly involved in low-risk group, which indicates that the low-risk group was immune activation and maybe respond better to immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of anti-angiogenic drugs in combination with immune checkpoint inhibitors is also attributed to the crosstalk of immune cells in the tumor microenvironment ( Ribatti et al, 2021 ). It has been shown that angiogenesis-related gene signatures in gastric cancer ( Ren et al, 2020 ; Qing et al, 2022 ), hepatocellular carcinoma ( Lv et al, 2021 ), and squamous carcinoma of multiple tissue types ( Qin et al, 2021 )can predict patient prognosis and elucidate the characteristics of the immune microenvironment to guide immunotherapy. Therefore, studying immune infiltration based on AG genes in cervical cancer can help to provide new predictive prognostic markers and reference for comprehensive treatment.…”
Section: Introductionmentioning
confidence: 99%